Being Bizzare: A New Composition Music | Being Bizzare: Sebuah Komposisi Musik Baru - I Nyoman Wiradarma Yoga; Hendra Santosa (GHURNITA: Jurnal Seni Karawitan, 2023)
The purpose of creating the musical composition Being Bizzare is to raise a physiological phenomenon about schizophrenia, namely an acute stress condition.. Like the story of John in the film "A Beautiful Mind" which tells the life journey of a John who suffers from schizophrenia. The life mechanism of a John was later appointed as a new musical composition with the title Being Bizzare with the regenerative nature of Gamelan Semarandana as the medium. Regenerative means to regenerate, focused on the melody element only, namely the melody part one is made up of a long melody which is a derivative of the melody part two, the melody part three is the opposite of the melody part one, the melody part four is derived from the melody part three. The creation method used was adopted from the book by Pande Made Sukerta, among others; organize content ideas, determine work ideas, and determine work. The application of this method resulted in four parts of a new musical composition, namely part one, part two, part three, and part four. As a new music, Being Bizzare is a work with the theme of psychology that aims to contextually inform schizophrenia disorders through musical works.